Cancer syndromes and therapy by stop-codon readthrough - Bordeira-Carriço, Renata (2019)
Several hereditary cancer syndromes are associated with nonsense mutations that create premature termination codons (PTC). Therapeutic strategies involving readthrough induction partially restore expression of proteins with normal function from nonsense-mutated genes, and small molecules such as aminoglycosides and PTC124 have exhibited promising results for treating patients with cystic fibrosis and Duchenne muscular dystrophy. Transgenic expression of suppressor-tRNAs and depleting translation termination factors are, among others, potential strategies for treating PTC-associated diseases. In this review, the potential of using readthrough strategies as a therapy for cancer syndromes is discussed, and we consider the effect of nonsense-mediated decay and other factors on readthrough efficiency.